Outcomes following operative vs. non-operative management of blunt traumatic pancreatic injuries: a retrospective multi-institutional study. Issue 1 (December 2016) - Addison, Poppy; Iurcotta, Toni; Amodu, Leo; Crandall, Geoffrey; Akerman, Meredith; Galvin, Daniel; Glazer, Annemarie; Christopherson, Nathan; Prince, Jose; Bank, Matthew; Sorrentino, Christopher; Cagliani, Joaquin; et al.
Abstract Background Traumatic pancreatic injuries are rare, and guidelines specifying management are controversial and difficult to apply in the acute clinical setting. Due to sparse data on these injuries, we carried out a retrospective review to determine outcomes following surgical or non-surgical management of traumatic pancreatic injuries. We hypothesize a higher morbidity and mortality rate in patients treated surgically when compared to patients treated non-surgically. Methods We performed a retrospective review of data from four trauma centers in New York from 1990–2014, comparing patients who had blunt traumatic pancreatic injuries who were managed operatively to those managed non-operatively. We compared continuous variables using the Mann-WhitneyU test and categorical variables using the chi-square and Fisher's exact tests. Univariate analysis was performed to determine the possible confounding factors associated with mortality in both treatment groups. Results Twenty nine patients were managed operatively and 32 non-operatively. There was a significant difference between the operative and non-operative groups in median age (37.0 vs. 16.2 years, P = 0.016), grade of pancreatic injury (grade I; 30.8 vs. 85.2%, P value for all comparisons <0.0001), median injury severity score (ISS) (16.0 vs. 4.0, P = 0.002), blood transfusion (55.2 vs. 15.6%, P = 0.0012), other abdominal injuries (79.3 vs. 38.7%, P = 0.0014), pelvic fractures (17.2 vs. 0.00%, P = 0.020), intensive care unit (ICU) admission (86.2 vs. 50.0%, P = 0.003), median length of stay (LOS) (16.0 vs. 4.0 days, P <0.0001), and mortality (27.6 vs. 3.1%, P = 0.010). Conclusions Patients with traumatic pancreatic injuries treated operatively were more severely injured and suffered greater complications than those treated non-operatively. The greater morbidity and mortality associated with these patients warrants further study to determine optimal triage strategies and which subset of patients is likely to benefit from surgery.